GROUND STATE OF NUCLEI IN THE BARIUM REGION WITHIN THE HIGHLY TRUNCATED DIAGONALIZATION APPROACH - Tung, N. Hoang; Hao, T. V. Nhan; Nizigama, A.; Le, N. Nhu (Hue University Journal of Science: Natural Science, 2017)
The ground state of some barium isotopes has been investigated in the framework of the parity-symmetry projection of the Highly Truncated Diagonalization Approach (HTDA), which is suited to treat the correlations in an explicitly particle-number conserving microscopic approach. A Skyrme energy-density function using the SkM∗interactions hasbeen considered to treat the particle-hole channel, whereas a density-independent δforce has been adopted for the residual interaction. The obtained results are compared with the previous calculations using the Woods-Saxon potentials.